Case Report: Predominant Tubulointerstitial Lupus Nephritis or the Combination With IgG4-Related Disease? - Tan, Ying; Qin, Yan; Yu, Xiao-juan; Xu, Rong; Wang, Su-xia; Zhou, Fu-de; Zhao, Ming-hui (Frontiers in Medicine, 2021)
Isolated or dominant tubulointerstitial lupus nephritis is rare. Here, we reported a 67-year-old man diagnosed with systemic lupus erythematosus (SLE) based on clinical and laboratory criteria, who was showing impaired renal function and non-nephrotic range proteinuria in the past 2 years. Renal biopsy showed almost normal glomeruli, but the tubulointerstitium showed “storiform” pattern with interstitial infiltration of IgG3 predominant plasma cells. Immunofluorescence showed linear and granular staining of IgG and C1q along TBM and interstitium. He started on medium dose of oral steroids and mycophenolate mofetil, which were gradually tapered. As a result, his renal function improved over a few days. Now, he continued on low dose steroids and mycophenolate mofetil with no evidence of relapse.